Early in vitro evidence indicates that deacetylated sialic acids modulate multi-drug resistance in colon and lung cancers via breast cancer resistance protein - Tuffour, Isaac; Amuzu, Setor; Bayoumi, Hala; Surtaj, Iram; Parrish, Colin; Willand-Charnley, Rachel (Frontiers in Oncology, 2023)
Cancers utilize sugar residues to engage in multidrug resistance. The underlying mechanism of action involving glycans, specifically the glycan sialic acid (Sia) and its various functional group alterations, has not been explored. ATP-binding cassette (ABC) transporter proteins, key proteins utilized by cancers to engage in multidrug resistant (MDR) pathways, contain Sias in their extracellular domains. The core structure of Sia can contain a variety of functional groups, including O-acetylation on the C6 tail. Modulating the expression of acetylated-Sias on Breast Cancer Resistance Protein (BCRP), a significant ABC transporter implicated in MDR, in lung and colon cancer cells directly impacted the ability of cancer cells to either retain or efflux chemotherapeutics. Via CRISPR-Cas-9 gene editing, acetylation was modulated by the removal of CAS1 Domain-containing protein (CASD1) and Sialate O-Acetyl esterase (SIAE) genes. Using western blot, immunofluorescence, gene expression, and drug sensitivity analysis, we confirmed that deacetylated Sias regulated a MDR pathway in colon and lung cancer in early in vitro models. When deacetylated Sias were expressed on BCRP, colon and lung cancer cells were able to export high levels of BCRP to the cell’s surface, resulting in an increased BCRP efflux activity, reduced sensitivity to the anticancer drug Mitoxantrone, and high proliferation relative to control cells. These observations correlated with increased levels of cell survival proteins, BcL-2 and PARP1. Further studies also implicated the lysosomal pathway for the observed variation in BCRP levels among the cell variants. RNASeq data analysis of clinical samples revealed higher CASD1 expression as a favorable marker of survival in lung adenocarcinoma. Collectively, our findings indicate that deacetylated Sia is utilized by colon and lung cancers to engage in MDR via overexpression and efflux action of BCRP.